Minimal benefit to extending the stroop Interference Task among individuals undergoing outpatient assessment. Issue 4 (4th July 2021) - Gradwohl, Brian D.; Spencer, Robert J.
Abstract: The third trial of Golden's Stroop Color and Word Test (SCWT), which involves identifying the color of words printed in a color that contrasts with its spelling, is usually limited to 45 seconds. Some authors have opined on the benefits of extending this portion of the test beyond 45 seconds to increase sensitivity to cognitive deficits and preliminary data among healthy individuals support this notion. This project examined possible benefits of extending the test beyond the standard 45 second time limit. Fifty-four veteran patients completed the SCWT as part of outpatient neuropsychological assessment. Speed of completing items within 45 seconds was compared to the speed of completing items beyond the first 45 seconds. A composite measure made of neuropsychological tests requiring speed and complex attention served as the criterion measure. Results indicated that extending the interference trial of the SCWT did not improve prediction on criterion measures beyond the standard 45 second SCWT. In conclusion, among individuals undergoing clinical evaluations, extending the SCWT beyond 45 seconds is unlikely to yield sufficient meaningful clinical data to offset the additional administration time and potential frustration to examinees.